Coral reefs : a natural history - Sheppard, Charles (Charles R. C.) (Princeton University Press, 2021)
An illustrated look at corals from around the world. Corals are among the most varied lifeforms on Earth, ranging from mushroom corals and leather corals to button polyps, sea fans, anemones, and pulse corals. Bridging the gap between plant and animal, these marine invertebrates serve as homes to reef fish and share symbiotic relationships with photosynthesizing algae, which provide corals with their nourishment. This stunningly illustrated book profiles the astonishing diversity of the world's coral groups, describing key aspects of their natural history and explaining why coral reefs are critical to the health of our oceans. Representative examples of corals have been selected to illustrate the broad range of species, and the book's lively and informative commentary covers everything from identification to conservation, making it an essential resource for marine biologists, divers, and anyone who is fascinated by these remarkable sea creatures. Features more than 200 exquisite color photos; highlights key aspects of corals and their natural history; features representative examples from around the world; and includes photos of rare and unusual species.